The Systematic Review of Shariah Governance in Islamic Banking System: A Meta-Synthesis Approach - Abdullah, Mahmoud; Said, Muhammad; Mufraini, Arief (Tapis: Jurnal Penelitian Ilmiah, 2022)
The purpose of this systematic review is to analyze and discuss Shariah Governance in the Islamic banking system from multiple integrative studies. The following study as a meta-synthesis approach employs the ENTREQ technique based on the inductive reasoning approach synthesized selected studies for the issue of Shariah Governance in the form of secondary data. A qualitative analysis research method is used to discuss the given issue systematically. This study employs a meta-synthesis approach of 40 research papers with 4 themes - Shariah audit, Shariah risk, Shariah supervisory, and Shariah Board which are the functions of Shariah Governance. The systematic review of synthesizing finds that Shariah Governance in Islamic banking has its strengths and weaknesses in improving the stability and performance of the Islamic Banking system based on the Shariah compliance requirements. In addition, the result and discussion of the present systematic review have two sections: synthesis finding and synthesis evaluation.